Fire behaviour of lightweight concrete units based on corn cob aggregate - Alves, Nuno (2015)
The search for alternative environmental friendly building solutions has been the goal of the scientific and the technical communities. Affordable, low energy and good quality water consumptions, and small amount of CO2 emission into the atmosphere are important attributes that these solutions have to fulfil. In general, applying organic products as raw building materials may be a step forward to achieve these attributes because they are likely of being abundant, local and renewable. For instance, rice husk ash blended cement has been proposed as a partial substitute of cement in mortar production.(...)